Do Countries with High Social Resilience Index (SRI) Manage Crises better? - Reuveni, Saada (Eximia, 2024)
Global shocks impact both developed and developing nations. Countries with higher State Resilience Index (SRI) are believed to be better equipped to handle such shocks than those with lower SRI. This study explores the relationship between SRI and GDP during economic crises. SRI assesses a nation’s readiness across various dimensions, while GDP measures economic performance and resilience. Analyzing 135 countries during three global crises: the Hi-Tech crisis in 2000; the food crisis of 2007-2008; and the COVID-19 pandemic. Countries were grouped by SRI levels: Group I comprised nations with low SRI (ranging from 4.7 to 6.3), and Group II included countries with high SRI ≥ 6.4. Data from the Fund for Peace (FFP) for the SRI indicator and The World Bank were used for the GDP indicator. Statistical analysis revealed that: (1) SRI alone does not dictate crisis response capability. (2) Countries with low SRI demonstrated unexpected resilience. (3) Nations with high SRI experienced more severe impacts. (4) An inverse relationship between SRI and GDP during crises was observed.